10 Redox Mediators in Organic Electrochemistry - Francke,R.; Prudlik,A.; Little,R. D. (Electrochemistry in Organic Synthesis, 2022)
This chapter is intended to serve as a mini-tutorial rather than a comprehensive review. Discussions focus upon fundamental aspects of electrochemically mediated electron transfer. Examples are provided to illustrate the major concepts and a sample procedure is provided.
Keywords: Referencework; indirect electrosynthesis; mediators; active and resting states; electron transfer; inner- and outer-sphere; follow-up reactions; catalytic current; turnover; Zeng mediators; Francke mediators; surface attachment; electrocatalysis; in-cell and ex-cell; minimizing energy waste; redox shuttle